Apigenin alleviates diabetic endothelial dysfunction through activating AMPK/PI3K/Akt/eNOS and Nrf2/HO‐1 signaling pathways - Lingchao Miao; Meng Sam Cheong; Chunxiu Zhou; Mohamed Farag; Wai San Cheang; Jianbo Xiao (Food Frontiers, 2023)
Abstract Apigenin (4′,5,7‐trihydroxyflavone) is a natural flavone reported to present anti‐diabetic and anti‐oxidative bioactivities. The effect of apigenin to mitigate endothelial dysfunction in diabetes remains to be investigated. In the present study, the vaso‐protective effect of apigenin as well as its underlying action mechanisms was investigated using in vitro‐ and in vivo‐based assays. Aortas were detached from C57BL/6J mice for ex vivo treatment, and primary rat aortic endothelial cells (RAECs) were cultured and further stimulated using high glucose (HG) with or without apigenin. In‐vivo diabetic model was established by feeding male C57BL/6J mice with a high‐fat diet (60% kcal% fat) for a total of 14 weeks, whereas the treatment group was orally administered apigenin (25 mg/kg/day) during the last 4 weeks. Exposure to HG (30 mM, 48 h) impaired acetylcholine‐induced endothelium‐dependent relaxation (EDR) in mouse aortas and induced oxidative stress with the downregulation of adenosine 5'‐monophosphate (AMP)‐activated protein kinase (AMPK)/phosphatidyl inositol 3‐kinase (PI3K)/protein kinase B (Akt)/endothelial nitric oxide synthase (eNOS) and nuclear factor erythroid 2‐related factor 2 (Nrf2)/heme oxygenase 1 (HO‐1) signaling pathways in aortas and RAECs. These impairments were reversed by apigenin treatments. However, the vaso‐protective effects of apigenin were abolished by Compound C (AMPK inhibitor) and wortmannin (PI3K inhibitor). Chronic oral administration with apigenin ameliorated EDR and reduced oxidative stress in the aortas of high‐fat diet (HFD)‐induced obese and diabetic mice. In conclusion, this study revealed that apigenin improved endothelial function and suppressed oxidative stress in the vasculature in diabetes through the activation of AMPK/PI3K/Akt/eNOS and Nrf2/HO‐1 pathways, suggesting its therapeutic potential as a natural dietary flavonoid against vascular diseases associated with diabetes.